Poly ε-Caprolactone Nanoparticles for Sustained Intra-Articular Immune Modulation in Adjuvant-Induced Arthritis Rodent Model - Ekta Singh; Riyaz Ali M. Osmani; Rinti Banerjee; Amr Selim Abu Lila; Afrasim Moin; Khaled Almansour; Hany H. Arab; Hadil Faris Alotaibi; El-Sayed Khafagy (MDPI AG, 2022)
Rheumatoid arthritis (RA) is a chronic inflammatory autoimmune disorder with synovitis and articular pathology as its primary expositions. Leflunomide (Lfd) is an anti-rheumatic drug that is effective in the treatment of RA, but displays severe side effects upon prolonged systemic administration. Local therapy might represent a promising strategy to treat rheumatoid arthritis without eliciting systemic adverse effects. In this study, leflunomide-loaded poly(ε-caprolactone) nanoparticles (Lfd-NPs) were prepared and assessed as a local drug delivery system capable of alleviating RA-associated inflammation. Lfd-NPs were optimized using the Quality by Design (QbD) approach, applying a 32 full factorial design. In vitro drug release from NPs was examined in simulated synovial fluid. In addition, the in vivo efficacy of Lfd-NPs was evaluated in the Adjuvant Induced Arthritis (AIA) rodent model. Sustained drug release in simulated synovial fluid was observed for up to 168 h. A gradual reduction in paw volume and knee diameter was observed over the course of treatment, indicating the regression of the disease. In addition, significant reductions in serum proinflammatory markers and cytokines, including the C-reactive protein (CRP), rheumatoid factor (RF), TNF-α, IL1-β, and IL-6, were verified upon treatment with Lfd-NPs, suggesting the modulation of immune responses at the pathological site. Most importantly, no remarkable signs of toxicity were observed in Lfd-NP-treated animals. Collectively, intra-articularly administered Lfd-NPs might represent a potential therapeutic alternative to systemically administered drugs for the treatment of rheumatoid arthritis, without eliciting systemic adverse effects.